Choroidal Osteoma in a Young Female – a Case Report: http://doi.org/10.36351/pjo.v37i2.1158 - Nisa, Mehr Un; Iqbal, Usama; Malik, Irfan Qayyum; Kanwal, Hira (Pakistan Journal of Ophthalmology, 2021)
We present a case of23 year old female, who presented with history of decreased central vision in the right eye for 3 months. Best corrected visual acuity was 6/36 OD and 6/9 OS. Anterior segment was normal OU. Fundus examination revealed a yellowish white peripapillary lesion extending up to the macula in the right eye. A similar lesion was seen in the left eye. OCT macula showed central macular thickness of 193 – 323 µm with cystoid spaces and 290 – 436 µm with serous retinal detachment in the right and left eye respectively. CT scan showed a hyper dense opacity similar to the bony tissue OU. All lab investigations were normal. The patient was diagnosed as a case of bilateral choroidal osteoma. After 6 months no progression or complication was noted. Key Words: Choroid, Osteoma, Choroidal Neoplasm.